Penggunaan Token Economies pada Anak untuk Meningkatkan Kedisiplinan dalam Menaati Peraturan - Mardina, Mutiara; Santoso, Meilanny Budiarti (Social Welfare Study Program, 2017)
The use of economies token for 12 years children aims at improving the discipline in complying with the rules at an orphanage institution. In the handled cases, the client has a problem against disciplinary, particularly related to the rules of the institutions, with the result that the client was often scolded. This article argues on the important of this token to uphold discipline guidance and mentoring. In this practice, the theory used is a behavioral therapy with the technique of economy token. The use of therapy behavioral methods intended to improve or maintain adaptive behavior, reduce or eliminate the maladaptive behavior, and reduce or eliminate the excessive behavior. By using economy token method, it is expected to help the client to have guidelines for improving discipline in complying with the rules. Based on 4 months of field assistance approach, the results of the assistance for 12 years old children who needs assistance in disciplinary training with economy token, communication and good thinking have become an important factor in relation to the development of a person, so that clients can reduce negative thoughts and changing dysfunctional thinking process.Keywords: discipline, behavioral therapy, economy token, 12 years old children.